COMMANDES PAR RETOUR D'ETAT NON LINEAIRE D'UN MOTEUR ASYNCHRONE - Soltani, Seddik; Allaoua, Kamal Kamar Eddine; Nacer, Heythem; Dhouib, Mohammed Seghir (université d'eloued, 2023)
"The paragraph is about controlling the speed and flux of a voltage-fed asynchronous machine using two nonlinear state feedback controls: nonlinear control and sliding mode control. Nonlinear control may be insufficient as it is less robust, especially when strict requirements are imposed on the precision and other dynamic characteristics of the system. Sliding mode control offers several advantages, including robustness, precision, and stability. In order to master the dynamic behavior of the control system, a comparative study of the two controls was conducted for variations in speed, load variations, and ultimately parameter variations. " "يتعلق األمر بالتحكم في سرعة وتدفق آلة غير متزامنة مُغذاة بالجهد ومُشغّلة بواسطة اثنتين من أوامر التغذية المرجعية غير الخطية، وهما القيادة غير الخطية والقيادة بوضع انزالقي. قد تكون القيادة غير الخطية غير كافية ألنها أقل متانة خاصةًعندما تكون المتطلبات المتعلقة بالدقة والخصائص الديناميكية األخرى للنظام صارمة. توفر القيادة بواسطة وضع االنزالق عدة مزايا، بما في ذلك القوة والدقة واالستقرار. لضبط سلوك النظام الديناميكي للتحكم، تم إجراء دراسة مقارنة لألوامر االثنين لتغيرات السرعة، وتغيرات الحمل، وأخيرًا التغيرات المعلمة. الكلمات المفتاحية : الماكينة غير المتزامنة (M.A.S) . القيادة غير الخطية. القيادة بوضع انزالقي. "
مذكرة ماستر الكتروميكانيكdes thèses électromécanique
Keywords: Asynchronous machine (A.M). nonlinear control. sliding mode control; الماكينة غير المتزامنة (M.A.S) . القيادة غير الخطية. القيادة بوضع انزالقي.